TRPM8 Channel Promotes the Osteogenic Differentiation in Human Bone Marrow Mesenchymal Stem Cells - Henao, Juan C.; Grismaldo, Adriana; Barreto, Alfonso; Rodríguez-Pardo, Viviana M.; Mejía-Cruz, Claudia Camila; Leal-Garcia, Efrain; Pérez-Núñez, Rafael; Rojas, Patricio; Latorre, Ramón; Carvacho, Ingrid; Torres, Yolima P. (Frontiers in Cell and Developmental Biology, 2021)
Various families of ion channels have been characterized in mesenchymal stem cells (MSCs), including some members of transient receptor potential (TRP) channels family. TRP channels are involved in critical cellular processes as differentiation and cell proliferation. Here, we analyzed the expression of TRPM8 channel in human bone marrow MSCs (hBM-MSCs), and its relation with osteogenic differentiation. Patch-clamp recordings showed that hBM-MSCs expressed outwardly rectifying currents which were increased by exposure to 500 µM menthol and were partially inhibited by 10µM of BCTC, a TRPM8 channels antagonist. Additionally, we have found the expression of TRPM8 by RT-PCR and western blot. We also explored the TRPM8 localization by immunofluorescence using confocal microscopy. Remarkably, hBM-MSCs treatment with 100M of menthol or 10M of icilin, TRPM8 agonists, increases osteogenic differentiation. On the contrary, 20M of BCTC, induced a decrease of osteogenic differentiation. These results suggest that TRPM8 channels are functionally active in hBM-MSCs and have a role in cell differentiation.